The quality of institutional performance according to the entrepreneurial management Applied research in the Municipality of Baghdad - salman, Dr. Fadheelah; Obeed, Hanan Ayad (The journal of contemporary issues in business and government, 2021)
The research aims to define the role of the entrepreneurial administration in achieving the quality of institutional performance in the Baghdad Municipality by defining the role of the administration at its levels in achieving the quality of institutional performance, as the researcher has reached, through theoretical framing and related studies, to build a hypothetical scheme that clarifies the relationship and influence of the research variables, as that The dimensions of the entrepreneurial management as an independent variable consists of four dimensions (strategic orientation, resource orientation, management structure, and orientation towards growth), while the quality of institutional performance is included as a dependent variable of three dimensions (financial performance, internal operations, customer satisfaction). These variables constitute the framework around which the research revolves, and the research community consists of those with responsible administrative positions within the upper and middle management level, as the sample included (general managers, assistants general directors, directors of departments and divisions) in the Baghdad Municipality Center. Collecting data and information, and the research produced a set of results, among which is that the entrepreneurial management plays a major role in the quality of institutional performance. Or the upper and middle management with the effectiveness of the entrepreneurial management whenever the quality of performance of the services provided in the Baghdad Municipality rises, as well as the weakness of the planning process of the administration and the lack of a clear vision in the activities and work of the researched organization.